2015
DOI: 10.1017/s000711451500375x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intestinal calcium and phosphate transport in young goats fed a nitrogen- and/or calcium-reduced diet

Abstract: Feeding ruminants a reduced N diet is a common approach to reduce N output based on rumino-hepatic circulation. However, a reduction in N intake caused massive changes in Ca and inorganic phosphate (P i ) homoeostasis in goats. Although a single dietary Ca reduction stimulated intestinal Ca absorption in a calcitriol-dependent manner, a concomitant reduction of Ca and N supply led to a decrease in calcitriol, and therefore a modulation of intestinal Ca and P i absorption. The aim of this study was to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 58 publications
(100 reference statements)
3
39
2
Order By: Relevance
“…Sample size (minimum n 7/group) was determined based on metabolic data from previous work (5) with a statistical power of 0•8 and α error of 0•05. Data are given as means with their standard errors if not stated otherwise and number of animals (n).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size (minimum n 7/group) was determined based on metabolic data from previous work (5) with a statistical power of 0•8 and α error of 0•05. Data are given as means with their standard errors if not stated otherwise and number of animals (n).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that decreased dietary protein intake caused massive changes in mineral homoeostasis and vitamin D metabolism in young goats (4,5) ; this being reflected by reduced levels of blood Ca, 1,25-dihydroxyvitamin D 3 (calcitriol) and insulin-like growth factor 1 (IGF1). Protein restriction was also shown to have an impact on Ca homoeostasis, IGF1 and vitamin D metabolism in monogastric species like humans and rats (6)(7)(8) .…”
mentioning
confidence: 99%
“…In goats kept on a low Ca diet or treated with vitamin D, duodenal Ca flux rates measured in Ussing chambers were significantly increased in some (Wilkens et al, 2012b) but not in all studies (Schröder et al, 1997;Sidler-Lauff et al, 2010). Higher flux rates and a more pronounced stimulation of transcellular Ca transport by dietary Ca restriction was accompanied by an increase in RNA, and protein expression of TRPV6 could be shown for the jejunum of goats indicating that this segment is more active for overall Ca absorption (Figure 6a) (Wilkens et al, 2012b;Elfers et al, 2015). Although the efficiency of net Ca absorption from the jejunum, measured by applying the Thiry-Vella loop technique, was increased in sheep with dietary Ca restriction (Abdel-Hafeez et al, 1982), this could not be demonstrated in protein expression studies and Ussing chamber experiments (Figure 6b) (Wilkens et al, 2011).…”
Section: Transcellular Intestinal Calcium Absorptionmentioning
confidence: 97%
“…Studies provide conflicting results on the intestinal absorption of Ca. 1,25-(OH) 2 D 3 -regulated proteins, essential for transcellular Ca absorption, have been identified in the small intestine of cattle (Yamagishi et al, 2006;Schröder et al, 2015), sheep (Schröder et al, 2001;Wilkens et al, 2009Wilkens et al, , 2011 and goats (Wilkens et al, 2012b;Elfers et al, 2015). However, Ca transport across ovine and caprine epithelia when determined in vitro in the absence of an electrochemical gradient appears to be very low compared to monogastric animals such as horses using the same methods ( Figure 5) (Wilkens et al, 2017).…”
Section: Transcellular Intestinal Calcium Absorptionmentioning
confidence: 99%
See 1 more Smart Citation